Land use and land cover change impact on forest carbon storage in Raktamala community forest, Nepal - Singh, Satish; Maharjan, Menuka; Das, Saroj Kumar (FORESTRY: Journal of Institute of Forestry, Nepal, 2025)
The Chure mountain range of Nepal is witnessing rapid changes in land use and land cover (LULC) due to increasing anthropogenic pressures, with significant implications for forest carbon storage. This study assesses the impact of the LULC changes on forest carbon in Raktamala Community Forest (CF), Saptari, using remote sensing, Geographic Information System and field-based methods. A total of 56 circular plots, with radii of 12.61 m for trees, 2.82 m for saplings and 1.87 m for soil, were established in the field. Tree diameter at breast height and height were measured, and carbon was estimated for aboveground biomass, belowground roots, saplings and soil. The results indicated a decline in forest cover from 54% in 2000 to 52% in 2022. The average carbon stock in 2022 was 156.60 ± 13.42 t ha⁻¹. Under a business-as-usual scenario, the estimated total forest carbon and CO2 equivalents for 2000 and 2010 were 28,537.52 t (104,447.3 t CO2) and 27,962.5 t (102,342.7 t CO2) respectively. These findings support the development of the Reducing Emissions from Deforestation and Forest Degradation baselines and sustainable forest management.